Opening up the valence shell: a T-shaped iron(I) metalloradical and its potential for atom abstraction - Ott, Jonas C.; Wadepohl, Hubert; Gade, Lutz H. (Angewandte Chemie. International edition, 2020)
A thermally stable, T-shaped, d7 high-spin iron(I) complex was obtained by reduction of a PNP-supported ferrous chloride. Paramagnetic NMR spectroscopy combined with DFT modeling was used to analyze the electronic structure of the coordinatively highly unsaturated complex. The metalloradical character of the compound was demonstrated by the formation of a benzophenone ketyl radical complex upon addition of benzophenone. Furthermore, the compound displays a rich chemistry as an oxygen-atom abstractor from epoxides, yielding a dinuclear, diferrous [Fe2O] complex.